Two new species of the Rhopalopsole magnicerca group (Plecoptera: Leuctridae) from China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2018)
Two leuctrid species of the Rhopalopsole magnicerca group are described as new, R. brevicula sp. nov. and R. jizushana sp. nov. from the Guangxi Autonomous Region of southern China, bordering Vietnam and Yunnan Province of southwestern China, respectively. The new species are compared with related taxa.